THE COORDINATION BETWEEN FRONT OFFICE DEPARTMENT AND HOUSEKEEPING DEPARTMENT AT PESONNA HOTEL PEKANBARU - Noprika Sestia Yanti; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Coordination is an effort to unify cooperative activities within a team itself as well as cooperation with other departments to achieve the same goals. This research was conducted at Pesonna Hotel Pekanbaru. The objective of this research is to find out how is the coordination system between the front office and housekeeping in the hotel. Pesonna hotel is a 3 star hotel which has 9 hotel branches in Indonesia. The forms of coordination between the front office of the department and the household department still have miscommunication but can still be improved, for the factors that affect work coordination between these departments have been running quite well, while the school-crowd in work coordination between these departments is in the form of form of communication between departments. To solve this problem, this study used a qualitative method by using four key informants as interviewees they area Front Office Supervisor, a Housekeeping Supervisor, a Front Desk Agent, and a Room Boy. In collecting the data, the writer used these followings techniques they are observation, interviews and documentation. Based on the result of the research, itrevealed that the coordination between the Front Office and Housekeeping has been going quite well, but still needs to be improved.Keywords : Coordination, Front Office, Housekeeping.